Analysis of Service Performance for Intermodal Facilities in The Area of Asrama Haji and Bumi Sriwijaya Stations - Haris, Willi; Malkhamah, Siti; Suparma, Latif Budi (Universitas Negeri Yogyakarta, 2024)
The integrated intermodal service system between the South Sumatra Light Rail Transit (LRT) and road-based transportation modes such as the Palembang Bus Rapid Transit (BRT) and Angkot Feeder Musi Emas still has shortcomings, particularly in the areas of the Asrama Haji and Bumi Sriwijaya Station. This research is conducted to observe the conditions of the physical facilities, payment integration, and schedules at both stations, as well as to examine the regulations in meeting the standards of ideal pedestrian physical facilities, which are then compared with passenger perceptions. This research utilizes the methods of crosstabulation analysis and Importance Performance Analysis (IPA). Crosstabulation analysis is used to determine the relationship between respondents' sociodemographic and their travel characteristics. Importance Performance Analysis (IPA) is used to assess passenger perceptions of the performance quality of intermodal facilities. Based on the research finding, according to passengers perceptions of 49 service attributes, there are 20 attributes that have a high level of importance but low performance, indicating the existence of three service provision needs that need to be prioritized for improvement. First, the provision of adequate and disability-friendly sidewalk facilities. Second, the provision of pedestrian crossing facilities. Third, the access to and from the node that is free from traffic conflicts. The recommended solutions include the construction of sidewalks connected to the node points, built higher than the road surface, installation of guiding block, barrier posts, and ramps at each end of the sidewalk, construction of an overpass (JPO) at the Asrama Haji Station and a pelican cross at the Bumi Sriwijaya Station, and the regulation of transit areas to prevent vehicles from parking and waiting at the entrance and exit points of the node.